2006
DOI: 10.1137/s0040585x97981524
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in the Time Synchronization Model

Abstract: We continue the study of the time synchronization model from arXiv:1201.2141 . There are two types i = 1, 2 of particles on the line R, with N i particles of type i . Each particle of type i moves with constant velocity v i . Moreover, any particle of type i = 1, 2 jumps to any particle of type j = 1, 2 with rates N −1 j α ij . We find phase transitions in the clusterization (synchronization) behaviour of this system of particles on different time scales t = t(N ) relative to N = N 1 + N 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Indeed, any mean-field model can be reduced to the corresponding model satisfying (9), by time and space rescaling. So, in all the proofs we do assume (9), in which case…”
Section: Theorem 3 Assume (1) Thenmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, any mean-field model can be reduced to the corresponding model satisfying (9), by time and space rescaling. So, in all the proofs we do assume (9), in which case…”
Section: Theorem 3 Assume (1) Thenmentioning
confidence: 99%
“…Subsequently to [5,6], there has been a line of work generally focused on modeling synchronization between elements (particles) of a large system, with mean-field interaction of the elements (particles), cf. [9][10][11][12][13][14].…”
Section: Other Related Workmentioning
confidence: 99%
“…There are already many particular examples justifying this belief. Thus the existence of the three time stages in the long time behavior was already proved for system with two types of deterministic particles and pairwise stochastic synchronizations [6], for discrete time random walks with a 3-particle anysotropic interaction [5], for continuous time random walks with symmetric k-particle synchronizations [7].…”
Section: Introductionmentioning
confidence: 87%
“…where averaging E S is taken over distribution of the map-valued random variable S introduced in (40). Hence by (42) we get…”
Section: Recurrent Equationsmentioning
confidence: 99%
“…The problem is to find different time scales (t = t N → ∞ as N → ∞) on which the synchronization system x(t N ) demonstrates completely different qualitative behaviour. The complete description of times scales was obtained for several models [40,[46][47][48]51]. For example, in [47] it was shown that the "BM N -model" passes three different phases before it reaches the final synchronization.…”
Section: Introductionmentioning
confidence: 99%